VMware vSphere 6.5 Cookbook. : Over 140 task-oriented recipes to install, configure, manage, and orchestrate various VMware vSphere 6.5 components. - Rajendran, Cedric (Packt Publishing, 2018)
VMware vSphere 6.5 is the next-generation infrastructure for next-generation applications. VMware vSphere is a complete and robust virtualization product suite that helps transforming data centers into simplified on-premises cloud infrastructures, providing for automation and orchestration of workload deployment and life cycle management of ...